Translating and Assessing the Validity and Reliability of Persian Version of the International Outcome Inventory for Hearing Aids (IOI-HA) - Abdollah Moossavi; Parisa Jalilzade Afshari; Erziyeh Lotfian; Enayatollah Bakhshi (Shiraz University of Medical Sciences, 2018)
Background: The aim of this paper was to prepare the Persian version of the unique International Edition of the self-report Hearing Aids questionnaire and to assess its validity and reliability. This questionnaire was chosen because of its simplicity, comprehensiveness for users, and usefulness, in comparison with other evaluations of outcomes hearing aids. Methods: Permission to translate International Outcome Inventory for Hearing Aids was obtained from its developer. The questionnaire was translated back into Persian, and then the translated version was retranslated to English by qualified individuals to assess its correspondence with the original version. After this stage, the content validity of the questionnaire was checked by nine audiology experts, with the results analyzed by Lawshe statistical method. In order to examine the structural reliability, the questionnaire was completed by 15 hearing impaired people and the necessary corrections were made according to the results. Finally, the final form was answered by 90 hearing-aid users, with the Cronbach's alpha statistical method utilized to analyze the results. In order to assess the test-retest reliability, the questionnaire was recompleted again by 30 subjects 1-2 weeks later, with the paired t-test correlation employed to evaluate the results. Results: The mean total score was 26.41 (SD=4.86). The test-retest results revealed no significant difference between the two groups. The internal consistency was 0.845 based on Cronbach's alpha, indicating acceptable test reliability. Conclusion: The present study demonstrated that the Persian version of the International Outcome Inventory for Hearing Aids possesses a good validity and reliability.